(untitled) (Scientific journal of the Fergana State University, 2023)
The article deals with the actual problem of expanding intercultural communicative competence in the educational process. Since higher education plays a key role in this process, this phenomenon is considered in English lessons. The purpose of the article is to highlight the stages of development of intercultural competence of students of non-linguistic higher education, thereby higher education involves a complex process of development of cognitive, social, emotional and cultural characteristics of the personality of future specialists. The article presents the main approaches and principles of the formation of intercultural communicative competence in the process of teaching students a foreign language. As a result of the rapid development of intercultural communication and global transformations taking place in the world since the late 90s. In the twentieth century, there is a need to create a personality with a new set of qualities and competencies that are urgently needed for rational functioning in a multicultural world.